Me Hubungan Antara Gaya Belajar Dengan Tingkat Prokrastinasi Siswa Kelas IX SMP Negeri 02 Kota Bengkulu: Pendahuluan Metode Penelitian, Pembahasan, Daftar Pustaka - Sri Saparahayuningsih; Natasya Aulia Gutawa; I Wayan Dharmayana (UNIVERSITAS BENGKULU, 2024)
The aim of this research is to find out how the level of procrastination of class IX students at SMP Negeri 02 Bengkulu City is related to their learning methods. Information was collected from the results of giving student questionnaires about procrastination and learning styles. The research sample consisted of 129 people using random sampling methodology. Contingency Correlation analysis was carried out on the data using the SPSS crosstab menu. With a correlation value of 0.286 and a significance level of p 0.117 (p>0.05), the research results show that there is no relationship between learning style and student procrastination. Because the learning style variable does not show a relationship, future researchers can choose the delay variable along with other factors. Keywords: learning style, procrastination, students